Pyrrhic victory : before you remove the knife - Upchurch, Daniel F. (Emerald Publishing Limited : Information Age Pub., 2022)
"This book is a continuation of the first text entitled "Pyrrhic Victory The Cost of Integration". This text focuses on identifying solutions to the issues that were addressed in the previous book and it takes a cohesive and empathic approach to deal with Black issues and issues affecting all minorities. This provocative text brings to life the quote "Before You Remove The Knife" and it closely examines the knife, the person or group who placed the knife in the wound, and the person or group that is responsible for removing it and healing the damaged and infected area. The text allows readers to travel back in time to reevaluate slavery, Jim Crow, and other significant moments that have created the current movement in the Black community. This book uses theoretical concepts to solve some of the problems in society, but most importantly this book brings awareness to our youth. It also supplies readers alternatives if their request for equity is not met and the peace and pieces are not provided to complete their historical puzzle. "There is not a typical response when it comes to addressing the injustice in America, just as there is no typical response to addressing the loss of an unarmed human by the hands of the police. The Black community is only asking for an Andy Griffin, not a Bull Conner." -Daniel F. Upchurch"--